Analisis Pengaruh Threat Emotion Konsumen, Brand Trust dan Corporate Image pada Keputusan Penggunaan Jasa - Gusti Noorlitaria Achmad; Rahmawati Rahmawati (Universitas Airlangga, 2020)
The Influence of Consumer Threat Emotion and Brand Trust and corporate image to the Buying Decision at Rumah Sakit Pertamina Balikpapan). This study aimed to analyze the influence of Threat Emotions and Brand Trust and corporate image to the Buying Decision. The independent variables in this study are threat emotions and brand trust, while the dependent variable in this study is buying decisions. The type of research that is used is quantitative research. The research was conducted on customers of Rumah Sakit Pertamina Balikpapan. The sampling technique used purposive sampling. Data analysis techniques in this study used regression analysis. This study shows that threat emotion does not have a significant positive effect on buying decisions, brand trust does have a significant positive effect on buying decisions, and corporate image has a positive and significant effect on buying decisions.